2008
DOI: 10.1158/0008-5472.can-07-2953
|View full text |Cite
|
Sign up to set email alerts
|

T-cadherin Supports Angiogenesis and Adiponectin Association with the Vasculature in a Mouse Mammary Tumor Model

Abstract: T-cadherin delineates endothelial, myoepithelial, and ductal epithelial cells in the normal mouse mammary gland, and becomes progressively restricted to the vasculature during mammary tumorigenesis. To test the function of T-cadherin in breast cancer, we inactivated the T-cadherin (Cdh13) gene in mice and evaluated tumor development and pathology after crossing the mutation into the mouse mammary tumor virus (MMTV)-polyoma virus middle T (PyV-mT) transgenic model. We report that T-cadherin deficiency limits ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
154
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(169 citation statements)
references
References 39 publications
14
154
0
Order By: Relevance
“…Western Blot Analysis-Frozen liver tissue and activated HSCs treated with fAd (5 g/ml), TIMP-1 (0.25 g/ml), CD63 antibody (0.25 g/ml), IgG antibody control (0.25 g/ml), and/or rat TIMP-1 recombinant protein was lysed and blotted as previously described (21). Membranes were incubated with antibodies against AMPK, p-AMPK, FAK, pFAK Y397 (Cell Signaling), ␣SMA (Sigma), CD63 (Secrotec), TIMP-1, and ␤1-integrin (Millipore) overnight in TBS-Tween containing 5% BSA at 4°C followed by HRP-conjugated secondary antibodies (Sigma) and visualization by chemiluminescence (SuperSignal West Pico; Thermo Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Western Blot Analysis-Frozen liver tissue and activated HSCs treated with fAd (5 g/ml), TIMP-1 (0.25 g/ml), CD63 antibody (0.25 g/ml), IgG antibody control (0.25 g/ml), and/or rat TIMP-1 recombinant protein was lysed and blotted as previously described (21). Membranes were incubated with antibodies against AMPK, p-AMPK, FAK, pFAK Y397 (Cell Signaling), ␣SMA (Sigma), CD63 (Secrotec), TIMP-1, and ␤1-integrin (Millipore) overnight in TBS-Tween containing 5% BSA at 4°C followed by HRP-conjugated secondary antibodies (Sigma) and visualization by chemiluminescence (SuperSignal West Pico; Thermo Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…However, as shown in numerous studies, Tcadherin expression is altered in tumor vessels: in Lewis carcinoma lung metastasis and F9 teratocarcinoma, PC-3 prostate cancer, in A673 rhabdomyosarcoma the expression of Т-cadherin is upregulated on endothelial cells of the blood vessels penetrating the tumor (Riou et al, 2006;Wyder et al, 2000), while no T-cadherin could be detected in the blood vessels of B16F10 melanoma lung metastasis (Wyder et al, 2000). Using mouse mammary tumor virus (MMTV)-polyoma virus middle T (PyV-mT) transgenic model with inactivated T-cadherin gene it was shown that T-cadherin deficiency limits mammary tumor vascularization and reduces tumor growth (Hebbard et al, 2008). In tumor neovascularization of hepatocellular carcinoma (Н ) T-cadherin is also upregulated in intratumoral capillary endothelial cells, whereas in surrounding tumor tissue as well as in normal liver nо Т-cadherin could be detected (Adachi et al, 2006).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Adiponectin acts as an inhibitory factor for the proliferation of human breast carcinoma cells and mammary tumor development (Arditi et al 2007;Dieudonne et al 2006;Grossmann et al 2008a;Hebbard et al 2008;Jarde et al 2008a;Kang et al 2005;Nakayama et al 2008;Pfeiler et al 2008;Wang et al 2006a). In vitro treatment with adiponectin at physiological concentrations attenuates the growth of an ER-negative human breast carcinoma MDA-MB-231 cells by inhibiting cell proliferation and inducing apoptosis (Kang et al 2005;Wang et al 2006a).…”
Section: Diversified Signaling Mechanisms Of Adiponectin: Cross-talkimentioning
confidence: 99%